Natural medicines : clinical efficacy, safety and quality - Ghosh, Dilip K.; Mukherjee, Pulok K. (Boca Raton, FL : CRC Press, 2020)
Globally, natural medicine has been considered as an important alternative to modern allopathic medicine. Although natural medicines are popular in society, only limited medicinal herbs have been scientifically evaluated for their potential in medical treatment. This book connects various aspects of the complex journey from traditional medicine to modern medicine. It provides information on topics including global regulations and regulatory hurdles, diverse nutritional challenges and potential health benefits, novel food innovations especially seed-to-clinic approaches, and future trends.
OCLC-licensed vendor bibliographic record.
Keywords: Herbs -- Therapeutic use -- Standards; Biological products -- Standards; MEDICAL / Alternative Medicine; MEDICAL / Nutrition